The Effect of Integrated Marketing Communication on Image, Satisfaction and Loyalty of Hotel Guests in Makassar City - Fitriana Fitriana; Jeni Kamase; Ramlawati Ramlawati; Zainuddin Rahman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
Research objectives are to examine and analyze the effects of: (1) Integrated marketing communication on image (2) Integrated marketing communication on satisfaction (3) Marketing communication on hotel guest loyalty, (4) Image on loyalty, (5) Satisfaction with loyalty, (6) ) Integrated marketing communication towards loyalty through image, (7) Integrated marketing communication towards loyalty through satisfaction. This research was conducted at a 4-star hotel in Makassar City. The population of this research is hotel guests. The sample is 234 respondents. The research data were analyzed using a structural equation modeling (SEM) program. The results showed that: (1) Integrated marketing communication has a significant influence onThis image shows that marketing communication that is applied directly can improve image (2) Integrated marketing communication has a significant effect on satisfaction, this shows that the higher the integrated marketing communication, the satisfaction will increase as well (3) Integrated marketing communication has a significant effect on loyalty, This shows that there is a good integrated marketing communication that will make hotel guests loyal (4) Image has a significant effect on satisfaction, this shows that image can directly create satisfaction (5) Satisfaction has a significant effect on loyalty, this shows that direct satisfaction can create loyalty (6) Integrated marketing communication has an indirect and significant effect on loyalty through images, this shows that integrated marketing communication can increase loyalty through images. (7) Integrated marketing communication has an indirect and significant effect on loyalty through satisfaction, this shows the higher the integrated marketing communication implemented by the hotel.will create hotel guest loyalty through satisfaction.